Analysis and assessment of divergence of final offers in negotiation using gamma and beta distribution. (31st May 2022) - Abraham, Sarin; Punniyamoorthy, Murugesan
The Final Offer Arbitration procedure is used to settle dispute where the parties involved propose different offers and an arbitrator choose one side's offer closer to his view of the fair offer as the final settlement. The competing parties try to guess the arbitrator's view of the final settlement and then attempt to propose the same offer as that of the arbitrator. But, this prediction cannot be done exactly and most of the time the players would only expect the arbitrator's preference to follow some distribution. This uncertainty about the arbitrator's choice leads to a divergence between the final positions arrived by the two players. In this paper, the divergence between the equilibrium strategies has been computed for two distributions, namely, the gamma and beta distribution which were hereto not considered by other researchers. The computed divergences for the gamma and beta distributions are compared with the known divergence of other distributions to check the applicability of these distributions in the Final Offer Arbitration game.